P242 The airway microbiota in human rhinovirus induced asthma exacerbation. (15th November 2016) - Wong, EHC; Dhariwal, J; Cuthbertson, L; James, P; Cox, M; Moffatt, M; Cookson, W; Johnston, S
Abstract : Background: Acute asthma exacerbations (AEs) cause significant morbidity. Up to 60% of AEs may be associated with respiratory viral infections, particularly human rhinoviruses (HRVs). The role of bacteria in AEs is unclear, yet antibiotics are frequently prescribed. Recent studies have demonstrated a greater abundance of potentially pathogenic bacteria (e.g. Haemophilus spp.) within the airway microbiota in asthma, whilst a greater abundance of commensals (e.g. Prevotella spp.) were observed in health. The aim of this study was to examine the changes within the airway microbiota in asthma in the context of a HRV-induced AE and evaluate if such changes correlate with clinical symptoms and lung function changes. Methods: Eleven moderate asthmatic (BTS step 3–4) and 12 healthy subjects were experimentally infected with HRV-16 and bronchoscopy was performed at baseline, 3 and 8 days following HRV-infection. Subjects completed daily symptom diary and spirometry. DNA was extracted from bronchoalveolar lavage and PCR amplification of the V3-V5 region of bacterial 16S rRNA gene was performed to evaluate microbiota community composition. Results: The microbiota composition did not significantly differ between healthy and asthmatic subjects at baseline, though healthy subjects exhibited significantly greater relative abundance of Prevotella spp. following HRV-infection (p < 0.05). At day 3 post-HRV infection, greater Prevotella spp. relative abundance was associated with lower symptom scores (R2 = 0.56, p < 0.05). In contrast, at day 8 greater Neisseria spp. relative abundance was associated with greater peak flow decline (R2 = 0.41, p < 0.05). Furthermore, HRV-16 viral load exhibited a significant linear relationship with the degree of microbiota community change (as measured by beta-diversity) (R2 = 0.61, p < 0.05). Conclusion: Following HRV infection, greater Prevotella spp. relative abundance was associated with less symptoms whilst greater Neisseria spp. was associated with greater peak flow decline, suggesting an imbalanced microbiota may exacerbate airway inflammation and ultimately severity of AE. Viral load significantly correlated with degree of microbiota community change, implying HRV infection may directly perturb the airway microbiota. Further studies are needed to confirm these findings and explore the roles of Prevotella spp. and Neisseria spp. in exacerbating airway inflammation.